Acquired Haemophilia A: A Review of What We Know - Mingot-Castellano ME; Rodríguez-Martorell FJ; Nuñez-Vázquez RJ; Marco P (Journal of Blood Medicine, 2022)
María Eva Mingot-Castellano,1 Francisco Javier Rodríguez-Martorell,1 Ramiro José Nuñez-Vázquez,1 Pascual Marco2 1Hematology Department, Hospital Universitario Virgen del Rocío. Instituto de Biomedicina de Sevilla (IBIS), Sevilla, Spain; 2General Medicine Department, Universidad Miguel Hernández, Instituto de Investigación Sanitaria y Biomédica de Alicante (ISABIAL), Alicante, SpainCorrespondence: María Eva Mingot-Castellano, Hematology Department, Hospital Universitario Virgen del Rocío, Instituto de Biomedicina de Sevilla (IBIS), Sevilla, Spain, Email mariae.mingot.sspa@juntadeandalucia.esAbstract: Autoantibodies against plasma coagulation factors could be developed by some individuals inducing severe and sometimes fatal bleedings. This clinical entity is called acquired haemophilia. It should be suspected in subjects with acute abnormal bleedings, without personal or familiar history of congenital bleeding disorders with an unexplained prolonged aPTT. It is rare disease, although its incidence may be underestimated due to the low knowledge about it by many specialists, the frequent use of anticoagulant or antiplatelet therapies in the affected population that can mask the diagnosis and, sometimes, a so withering effect that avoid its confirmation. Mortality ranges between 9% and 33% depending on the series in the first 2 months after diagnosis. This mortality is attributed in up to 40% of the cases to infections in the context of immunosuppressive treatments used to eliminate the inhibitor. Factor VIII levels below 1% and high inhibitor titers are conditions of worse response rates. Advanced age, patient’s ECOG, and underlying conditions are key prognostic factors for response to treatment and patient survival. To reduce morbidity and mortality in these patients, it is important to have clinical knowledge and access to guidelines to achieve an early diagnosis and to optimize the haemostatic and immunosuppressive treatment. This review aims to contribute to the dissemination of basic concepts on the epidemiology etiopathogenesis, diagnosis, treatment and management of these patients, as well as risk factors to get remission and the longest overall survival to allow individualized care. Especial awareness will be proposed in patients with some underlying conditions like cancer, autoimmune diseases, children, pregnancy or drugs.Keywords: acquired haemophilia, inhibitors, coagulopathy, autoimmune, bleeding